2018
DOI: 10.1053/j.jvca.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Patient Length of Stay on the Intensive Care Unit Following Cardiac Surgery: A Logistic Regression Analysis Based on the Cardiac Operative Mortality Risk Calculator, EuroSCORE

Abstract: This analysis of an extensive data set shows that patient LOS in ICU after cardiac surgery in a single center can be predicted accurately using the simple cardiac operative risk scoring tool EuroSCORE. Using such predictions has the potential to improve ICU resource management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…In this study, nine predictive models were established to predict the progression of urinary protein in patients with chronic kidney disease, and model selection was based on several currently and frequently adopted predictive model types. For the linear model, the logistic regression model (LR) [14, 15], the elastic network model (Elastic Net) [1618], the lasso regression model (Lasso) [19], and the ridge regression model (Ridge) were selected [2022]. The neural network model (NN) [23] was chosen because it is an important class of nonlinear prediction models [24] and has been reported to predict CKD.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, nine predictive models were established to predict the progression of urinary protein in patients with chronic kidney disease, and model selection was based on several currently and frequently adopted predictive model types. For the linear model, the logistic regression model (LR) [14, 15], the elastic network model (Elastic Net) [1618], the lasso regression model (Lasso) [19], and the ridge regression model (Ridge) were selected [2022]. The neural network model (NN) [23] was chosen because it is an important class of nonlinear prediction models [24] and has been reported to predict CKD.…”
Section: Methodsmentioning
confidence: 99%
“…Model selection was based on several currently and frequently adopted predictive model types. For example, the linear LR model [64] and SVM model have been widely adopted in many clinical applications, such as for CKD disease prediction [65]. The DT model [66] is based on a radial basis function neural network and support vector machine coupled with firefly algorithm techniques; the XGboost and MLP models have also been used in clinical research [65,67].…”
Section: Model Construction In the Training Setmentioning
confidence: 99%
“…[9,12] In one of the most largest study, including 18,377 consecutive patients, the AUC for prolonged hospitalization at ICU for both ESA and ESL was 0.73. [13] Atashi et al [8] indicated the importance of identifying reliable risk scores for prediction of prolonged hospitalization at ICU in a large systematic review published in 2018. They pointed difficulties in defining new risk factors and possible advantages of validating currently available risk scores.…”
Section: Discussionmentioning
confidence: 99%